KEBIJAKAN PENCEGAHAN GERAKAN ISIS DI INDONESIA: PENDEKATAN SYSTEM DYNAMICS - Setiawan, Asep (Jurnal Mandala, 2018)
slamic State of Iraq and Syria (ISIS) launch a campaign to recruit new followers around the world. ISIS uses direct and indirect pattern of recruitment with social media which is called cyber jihad and its network in many countries. With system dynamics approach, the article tries to understand how Indonesiaâs government to response ISIS aggressive policy to expand its influence and its followers. It shows that if Indonesia does not act to prevent ISIS expansion, the country will be further target of this radical movement. Indonesia government employs deradicalisation program and military operation will give impact to minimize influence and recruitment ISIS.